Capacity credit of microgeneration and microgrids - Costa, Paulo Moisés (2017)
The recent development of the concept of microgrid (μGrid), associated to the emergent interest in microgeneration (μGen), has raised a number of challenges regarding the evaluation of the technical, economical and regulatory impacts of a high penetration of this kind of solutions in the power systems. In this paper, the topic of security of supply is addressed, aiming at evaluating the influence of μGen and μGrids in the medium- and long-term availability of generation to serve the forecasted load. A Monte-Carlo based methodology is used to evaluate this influence and to assess the capacity credit of those entities.